Ultrafast Spectroscopy of Plasmons and Free Carriers in 2D MXenes. Issue 8 (22nd December 2022) - Colin‐Ulloa, Erika; Fitzgerald, Andrew; Montazeri, Kiana; Mann, Javery; Natu, Varun; Ngo, Ken; Uzarski, Joshua; Barsoum, Michel W.; Titova, Lyubov V.
Abstract: 2D MXenes have diverse and chemically tunable optical properties that arise from an interplay between free carriers, interband transitions, and plasmon resonances. The nature of photoexcitations and their dynamics in three different members of the MXene family, Ti3 C2, Mo2 Ti2 C3, and Nb2 C, are investigated using two complementary pump‐probe techniques, transient optical absorption, and time‐resolved terahertz (THz) spectroscopy. Measurements reveal pronounced plasmonic effects in the visible and near‐IR in all three. Optical excitation, with either 400 or 800 nm pulses, results in a rapid increase in lattice temperature, evidenced by a pronounced broadening of the plasmon mode that presents as a plasmon bleach in transient absorption measurements. Observed kinetics of plasmon bleach recovery provide a means to monitor lattice cooling. Remarkably slow cooling, proceeding over hundreds of picoseconds to nanoseconds time scales, implies MXenes have low thermal conductivities. The slowest recovery kinetics are observed in the MXene with the highest free carrier density, viz. Ti3 C2, that supports phonon scattering by free carriers as a possible mechanism limiting thermal conductivity. These new insights into photoexcitation dynamics can facilitate their applications in photothermal solar energy conversion, plasmonic devices, and even photothermal therapy and drug delivery. Abstract : Photoexcitations in Ti3 C2, Mo2 Ti2 C3, and Nb2 C, are investigated using transient optical absorption and time‐resolved terahertz spectroscopy. All three MXenes exhibit pronounced plasmonic effects in the visible and near‐IR. Optical excitation rapidly increases lattice temperature, evidenced by a phonon bleach in transient absorption measurements. Slow cooling, proceeding over hundreds of picoseconds to nanoseconds time scales, is attributed to their low thermal conductivities.